Homologous recombination deficiency test validation in patients with high-grade advanced ovarian cancer - Angelica Nogueira Rodrigues; Andreza Karine de Barros Almeida Souto; Diocésio Alves Pinto de Andrade; Larissa Müller Gomes; Sandra Satie Koide; Renata de Godoy e Silva; Bruno Batista de Souza; Juliana Doblas Massaro; Andréia Cristina de Melo; Andrea Morais Borges; Camila Giro; Carlos Augusto Vasconcelos de Andrade; et al. (Frontiers in Molecular Biosciences)
BackgroundAlong with BRCA mutation status, homologous recombination deficiency (HRD) testing is a prognostic and predictive biomarker for poly-ADP-ribose polymerase (PARP) inhibitor therapy indication in high-grade epithelial ovarian, fallopian tube, or peritoneal cancer. Approximately 50% of high-grade serous ovarian cancers exhibit HRD, even in the absence of germline or somatic BRCA1/2 loss-of-function mutations. In this scenario, access to a validated diagnostic HRD test can optimize treatment selection and increase the effectiveness of the intervention.ObjectiveTo technically validate an in-house next-generation sequencing (NGS)-based HRD test, QIAseq Custom Panel (QIAGEN), by comparing it with the reference assay, MyChoice CDx® Plus HRD (Myriad Genetics), which is used in routine care.MethodsThis is a prospective cohort study conducted at the Oncoclínicas Precision Medicine (OCPM) laboratory using samples from patients with advanced or relapsed platinum-sensitive ovarian cancer eligible for HRD testing in a diagnostic clinical setting at Oncoclínicas and Co. We assessed the performance of the in-house test (GS Focus HRD) using Cohen’s kappa statistic to measure agreement with the gold standard assay (MyChoice® HRD Plus CDx) in HRD status classification, along with other accuracy metrics.ResultsIn total, 41 samples were analyzed (20 HRD-positive, 19 HRD-negative, and 2 inconclusive results with the MyChoice® HRD Plus CDx assay). The GS Focus HRD test demonstrated high concordance for HRD status with the reference test (kappa: 0.8 and 95% CI: 0.60–0.98). Overall accuracy, sensitivity, and specificity were 90%. Six samples had BRCA1/2 mutations identified by the MyChoice® HRD Plus CDx, all of which were detected by the GS Focus HRD test.ConclusionIn summary, the results demonstrate substantial agreement and high accuracy of the NGS-based GS Focus HRD test compared to MyChoice® HRD Plus CDx. Our in-house assay is eligible for diagnostic test approval and market access as per Brazilian regulations.